CYP450 and drug efflux transporters polymorphism influence clinical outcomes of Thai osimertinib-treated non-small cell lung cancer patients - Majam, Teerapat; Sukasem, Chonlaphat; Reungwetwattana, Thanyanan; Chansriwong, Phichai; Atasilp, Chalirmporn; Trachu, Narumol; Thamrongjirapat, Thanaporn; Sukprasong, Rattanaporn; Meanwatthana, Jennis (Frontiers in Pharmacology, 2023)
Background: Osimertinib has shown greater efficacy than standard epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and fewer grade 3 or higher adverse drug reactions (ADRs) in patients with advanced non-small-cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations. However, the clinical outcomes of osimertinib treatment vary depending on the patient's ethnicity. Therefore, further research is necessary to evaluate the impact of single nucleotide polymorphisms (SNPs) in cytochrome P450 (CYP450) and drug transporters on the therapeutic outcomes and ADRs to osimertinib in Thai patients, to provide improved pharmacological treatments for cancer patients. This retrospective and prospective cohort study enrolled 63 Thai patients with NSCLC treated with 80 mg of osimertinib once daily as monotherapy. Seventeen SNPs in candidate genes related to drug metabolism and transport pathways were analyzed in each patient. We identified six SNPs (rs2231142 and rs2622604 in ABCG2, rs762551 in CYP1A2, rs1057910 in CYP2C9, rs28371759 in CYP3A4, and CYP2A6 deletion polymorphism (CYP2A6*4)) that significantly increased the incidence of ADRs. In addition, we found two SNPs (rs2069514 in CYP1A2 and rs1057910 in CYP2C9) that significantly decreased the median TTF, and two SNPs (rs28399433 in CYP2A6 and rs1057910 in CYP2C9) that significantly decreased the median progression-free survival (PFS). Specifically, we found that one of these SNPs (rs1057910 in CYP2C9) influenced ADRs, TTF, and PFS. Additionally, SNPs in the CYP2A6 heterozygous variant (non4/*4) significantly increased ADR incidence, leading to a high frequency of dose reduction (27.0%). Our study demonstrated significant SNPs associated with increased ADR incidence, decreased PFS, and decreased TTF in Thai patients with NSCLC treated with osimertinib. The CYP2C9 (*3) and CYP2A6 (*4) allele frequencies differed between ethnicities and were associated with an increased incidence of ADRs. These findings highlight the importance of considering genetic factors in NSCLC treatment and may facilitate personalized medicine approaches. Moreover, our study showed a higher incidence of ADRs than the previous trials, including FLAURA and AURA2, and a higher frequency of dose reduction than reported in the AURA 3 trial, possibly due to genetic differences among the study populations.